Extortion experiences of recent adult immigrants from Latin America: self-reported prevalence, associated costs, and current mental health - Laura Vargas; C. Neill Epperson; Therese S. Richmond; Shadi Sharif; Lily Berkowitz; Zachary Giano; Stephen Hargarten; Mark Ungar; Eugenio Weigend-Vargas; Joseph Sakai (Injury Epidemiology, 2024)
Abstract Violence across Latin America is an increasingly important factor influencing migration to the US. A particular form of violence that is experienced by many Latinx migrants is extortion. This research analyzes the extortion experiences of Latinx immigrant adults arriving at the US southern border and the impact these experiences have on mental health. We find that on average, participants paid $804 in extortion during their migration. The most common perpetrators of extortion in our study were police followed by immigration officials throughout Latin America. Pregnant participants were less likely to experience extortion and adults traveling with children were more likely to be extorted. Participants who were extorted for money reported significantly greater severity of post-traumatic stress disorder (PTSD) symptoms compared to those who were not extorted. This research is the first of its kind to analyze extortion experiences among Latinx immigrants to the US, quantifying the prevalence, amounts paid, countries where extortion occurs, and perpetrators of extortion. In addition, extortion experiences are associated with negative effects on the mental health of newly arrived Latinx immigrants to the US. Based upon these findings, we recommend that extortion should be considered a significant stressor in the migrant experience, particularly for those adults traveling with children.